Hormone Replacement Therapy and Circulating ICAM-1 in Postmenopausal Women - Scarabin, Pierre-Yves; Alhenc-Gelas, Martine; Oger, Emmanuel; Plu-Bureau, Geneviève (Thrombosis and Haemostasis, 1999)
Hormone replacement therapy may reduce the risk of coronary heart disease but underlying mechanism has not been adequately explained. Recent data suggest that intercellular adhesion molecule 1 (ICAM-1) plays a critical role in early stage of atherosclerosis and may serve as a molecular marker for the development of arterial disease. We investigated the effects of oral and transdermal cyclic oestradiol combined with progesterone on plasma concentration of soluble ICAM-1 (sICAM-1). Thirty-seven healthy postmenopausal women were randomly assigned to receive either oral estradiol valerate or transdermal estradiol both combined with micronized progesterone or no hormonal treatment. Plasma sICAM-1 was assayed at baseline and after a 6-month period. Oral but not transdermal estradiol regimen significantly decreased mean value of sICAM-1 compared with no treatment. Differences in sICAM-1 levels between active treatments were significant. There were no significant changes in mean values of fibrinogen between the three groups. Our results show a favorable effect of oral estrogen plus progesterone on a soluble marker of vascular inflammation and may provide plausible explanation for a cardioprotective effect of hormone replacement therapy among healthy postmenopausal women.